Benchmarking of the Oxford Nanopore MinION sequencing for quantitative and qualitative assessment of cDNA populations - Oikonomopoulos, Spyros; Wang, Yu Chang; Djambazian, Haig; Badescu, Dunarel; Ragoussis, Jiannis (Scientific reports, 2016)
To assess the performance of the Oxford Nanopore Technologies MinION sequencing platform, cDNAs from the External RNA Controls Consortium (ERCC) RNA Spike-In mix were sequenced. This mix mimics mammalian mRNA species and consists of 92 polyadenylated transcripts with known concentration. cDNA libraries were generated using a template switching protocol to facilitate the direct comparison between different sequencing platforms. The MinION performance was assessed for its ability to sequence the cDNAs directly with good accuracy in terms of abundance and full length. The abundance of the ERCC cDNA molecules sequenced by MinION agreed with their expected concentration. No length or GC content bias was observed. The majority of cDNAs were sequenced as full length. Additionally, a complex cDNA population derived from a human HEK-293 cell line was sequenced on an Illumina HiSeq 2500, PacBio RS II and ONT MinION platforms. We observed that there was a good agreement in the measured cDNA abundance between PacBio RS II and ONT MinION (r pearson = 0.82, isoforms with length more than 700bp) and between Illumina HiSeq 2500 and ONT MinION (r pearson = 0.75). This indicates that the ONT MinION can sequence quantitatively both long and short full length cDNA molecules.